Microorganism-regulated autophagy in gastrointestinal cancer - Xu,Jun-Yu; Fan,Jiao-Xiu; Hu,Min; Zeng,Jun (PeerJ, 2023)
Gastrointestinal cancer has always been one of the most urgent problems to be solved, and it has become a major global health issue. Microorganisms in the gastrointestinal tract regulate normal physiological and pathological processes. Accumulating evidence reveals the role of the imbalance in the microbial community during tumorigenesis. Autophagy is an important intracellular homeostatic process, where defective proteins and organelles are degraded and recycled under stress. Autophagy plays a dual role in tumors as both tumor suppressor and tumor promoter. Many studies have shown that autophagy plays an important role in response to microbial infection. Here, we provide an overview on the regulation of the autophagy signaling pathway by microorganisms in gastrointestinal cancer.
Keywords: Autophagy; Microorganisms; Gastrointestinal cancer